Electromyographic Analysis of Gluteus Maximus, Gluteus Medius, Hamstring and Erector Spinae Muscles Activity During the Bridge Exercise With Hip External Rotation in Different Knee Flexion Angles in Healthy Subjects - Lee, Kyung-eun; Baik, Seung-min; Yi, Chung-hwi; Kim, Seo-hyun (Han'guk Chŏnmun Mulli Ch'iryo Hakhoe chi = Journal of the Korean Academy of University Trained Physical Therapists, 2019)
Background: The bridge exercise targets the gluteus maximus (Gmax) and gluteus medius (Gmed). However, there is also a risk of dominant hamstring (HAM) and erector spinae (ES) muscles. Objects: To analyze the muscle activity the of Gmax, Gmed, HAM and ES during the bridge exercise with and without hip external rotation in different degrees of knee flexion. Methods: Twenty-three subjects were participated. The electormyography (EMG) activity of the Gmax, Gmed, HAM and ES muscles was recorded during the exercise. The subjects performed the bridge exercise under four different conditions: (a) with 90˚ knee flexion, without hip external rotation (b) with 90˚ knee flexion, with hip external rotation (c) with 135˚ knee flexion, without hip external rotation (d) with 135˚ knee flexion, with hip external rotation. Results: There was no significant interaction effect between the degree of knee flexion and hip external rotation. There was a significant main effect for degree of knee flexion in Gmax, HAM muscles activity. Gmax muscle activity was significantly greater in the 135˚ knee flexion position than in the 90˚ knee flexion position (p<.001). While HAM muscle activity was significantly less in 135˚ knee flexion position than in the 90˚ knee flexion position (p<.001). ES muscle activity was significantly less in the 135˚ knee flexion position than in the 90˚ knee flexion position (p=.002). The activity of both the Gmax and Gmed muscles was significantly greater with hip external rotation (p<.001 and p=.005, respectively). Conclusion: For patients performing the bridge exercise, positioning the knee in 135° of flexion with hip external rotation is effective for improving Gmax and Gmed muscle activity while decreasing HAM, and ES muscle activity. KCI Citation Count: 0